2011
DOI: 10.1053/j.seminoncol.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Pediatric Cancer Surveillance Using Serial Computed Tomography: Evaluation of Organ Absorbed Dose and Effective Dose

Abstract: Computed tomography (CT) is used extensively in cancer diagnosis, staging, evaluation of response to treatment, and in active surveillance for cancer reoccurrence. A review of CT technology is provided, at a level of detail appropriate for a busy clinician to review. The basis of x-ray CT dosimetry is also discussed, and concepts of absorbed dose and effective dose are distinguished. Absorbed dose is a physical quantity (measured in milliGray) equal to the x-ray energy deposited in a mass of tissue, whereas ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Three independent parameters were extrapolated from all the binarized ROIs for the multimodal and multiscale comparative analysis [ 7 , 20 ]. The bone volume fraction (BVF) was calculated as the ratio between bone volume and total volume.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three independent parameters were extrapolated from all the binarized ROIs for the multimodal and multiscale comparative analysis [ 7 , 20 ]. The bone volume fraction (BVF) was calculated as the ratio between bone volume and total volume.…”
Section: Methodsmentioning
confidence: 99%
“…The segmentation of the µCT images was straightforward, since the contrast was high and the voxel size was smaller than the trabecular thickness. Three independent parameters were extrapolated from all the binarized ROIs for the multimodal and multiscale comparative analysis [7,20]. The bone volume fraction (BVF) was calculated as the ratio between bone volume and total volume.…”
Section: Bone Morphological Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each scan provides approximately 10 to 15 millisievert of ionizing radiation, the equivalent of 5 years of background radiation. [6][7][8] The diagnostic interventions used can result in deleterious health effects 9 ; the repeating schedule of these scans significantly increases radiation exposure in a young patient population with an otherwise long life expectancy and may contribute to an increased risk of second malignant neoplasms (SMNs), as suggested by population-based studies. 10,11 Miglioretti et al 11 reported the lifetime attributable risk of cancer per 10,000 CT scans to be between 0.5 and 30.5, with the highest risk of radiation-induced solid tumor development with abdomen/pelvic CT, which is frequently used in the surveillance of MGCTs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CT in a cancer surveillance protocol was used as an example of a paediatric patient who had kidney cancer, with surgery and radiation therapy. The active use of diagnostic CT scans lead to a total of 50 CT scans during a seven year period and it was estimated that the patient received an organ dose of 114 mGy to 872 mGy [11].…”
Section: Introductionmentioning
confidence: 99%